Analisis Strategi Komunikasi Politik Public Figure dalam Mendapatkan Kursi di DPD Jawa Barat Pada Tahun 2024 : (Studi Kasus Alfiansyah Komeng) - Mohammad Rafatta Umar; Muhammad Sulthan Fatih; Sabrina Shafa Qonita; Muhammad Prakoso Aji; Dinda Rizka Maulany Kurnia; Syahwa Fitria Kurniawan (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
Alfiansyah Komeng's participation in the West Java Regional Representative Council election in 2024 was a surprising phenomenon. 5.3 million votes were achieved, which led him to occupy the seat of the West Java Regional Representative Council. One of the things that attracted the attention of many people was the use of an informal photo by Alfiansyah Komeng to be posted on the voting paper. This research seeks to analyze the personal branding that Alfiansyah Komeng has built to win a seat in the West Java Regional Representative council in 2024 and how social media plays a role in shaping Alfiansyah Komeng's image. The theories used in this research are framing theory and personal branding. The method used in this research is a qualitative approach with literature studies from books and previous studies. Information from interviews scattered on the internet and other internet data is also taken in this research. The result of this research is that Komeng only focuses on building his personal branding with an image as a comedian and almost no branding that describes him as a politician.